KINERJA PEGAWAI BERDASARKAN KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA - Lutfa, Yuyinah (Journal of Innovation in Business and Economics, 2012)
Goals to be achieved in this study was to determine the effect of leadership, motivation and environment affect the performance of employees in Malang Regency Community Empowerment Board and the dominant variables affecting the performance of employees in Malang Regency Community Empowerment Board is motivation. Therefore, based on the results of the analysis in this study, then the suggestions can be given is the Community Empowerment Board should leader Malang more attention to issues of leadership and motivation to employees, because it can improve performance. Guidance, supervision and education of employees should be synergized with the interests of the institution, so as to support the motion dynamics of performance measures and work environment needs to be improved to enhance the performance of employees.